Screening of winery and olive mill wastes for lignocellulolytic enzyme production from Aspergillus species by solid-state fermentation - Salgado, José Manuel (2014)
Wastes from olive oil and wine industries (as exhausted grape marc, vineshoot trimmings, two-phase olive mill waste, vinasses, and olive mill wastewater) were evaluated for lignocellulolytic enzyme production (as endocellulases, endoxylanases, and feruloyl esterases) by solid-state fermentation (SSF) with Aspergillus niger, Aspergillus ibericus, and Aspergillus uvarum. To study the effect of different solid medium composition and time in enzyme production, a PlackettBurman experimental design was used. Variables that had a higher positive effect in lignocellulolytic enzyme production were urea, time, and exhausted grape marc. The maximum values of enzymatic activity per unit of substrate dry mass were found with A. niger for feruloyl esterase. Enzymatic extracts from SSF with A. niger achieved maximum feruloyl esterase activity (89.53 U/g) and endoxylanase activity (3.06 U/g) and with A. uvarum for endocellulase activity (6.77 U/g). The enzyme cocktails obtained in the SSF extracts may have applications in biorefinery industries.